(untitled) (Journal of International Studies, 2016)
Fundamental rights have importance, concern and challenges to societies and states at local and international levels. Those are, however, more in developing states and democracies. Many Nigerian citizens especially civilians and the poor have gone into despair for most of the citizens’ rights exist only on paper and are not realistic. This paper investigated the fundamental rights of Nigerian citizens: provisions, enforcement, and myth in these rights; reality and manoeuvre by various stake holders in human rights provisions; enforcement and safeguard. The study used secondary sources of data. It is found that fundamental rights provisions and enforcement in Nigeria are constrained by military rule, poor or no political will and commitment, poor constitutional provisions, poor legal aid and services, ignorance of the existing laws and provisions, deliberate acts to thwart the arm of justice, corruption, judicial incompetence, inefficient justice system, socio-cultural provisions, poverty, state aligned threats and intimidations. The study recommends extensive and intensive education and enlightenment to citizens, full monitoring and strict compliance with provisions on rights, broader and functional legal aid services especially to the poor and the ignorant, revamping Nigeria’s justice system to reflect current realities and strict compliance with the rules of engagement by the armed forces, and reviewing laws such as the Penal and Criminal code laws to co-opt new trends and realities.